Stress Analysis of Waterproof Single-layer Lining Composite Structure in Metro Tunnels Based on Intermediate Layer Theory - WEN Shuyi; DENG Yisan (Chengshi guidao jiaotong yanjiu, 2024)
Objective The application of sprayed waterproof membranes can enable composite action between the shotcrete and the waterproof membrane in metro tunnel linings. However, there is currently no design guidance or reference literature for analyzing waterproof single-layer lining composite structures. A design method is proposed to determine the thickness of the tunnel single-layer lining composite structure and to allocate bending moments according to stiffness based on intermediate layer theory. Method The theoretical derivation of equivalent thickness and bending moment distribution is first conducted. The Qingdao Metro Line 1 Xizhen Station is selected for calculating the equivalent thickness and bending moment distribution of each layer, yielding theoretical analytical solutions. To verify the accuracy of the theory, numerical simulation analysis is performed using the finite element Ansys, comparing and discussing the equivalent thickness and bending moment distribution for different second layer shotcrete thicknesses in tunnels. Finally, indoor experiments are conducted to perform four-point beam tests comparing structures with and without a sprayed waterproof membrane. The equivalent thickness of the composite structure is calculated through the reverse deduction of the bending strength reduction ratio of the intermediate layer structure. Result & Conclusion The proposed design method can accurately determine the equivalent thickness and bending moment distribution, proving to be both reasonable and feasible.